(untitled) (Global Journal of Human-Social Science, 2022)
Child sexual abuse is a concern around the world. It really is a ubiquitous, ongoing, and critical problem. Child sexual abuse can completely cure the trauma and tissue damage over time, but medical and psychological consequences can develop later in life. Here related contagious diseases (e.g., HIV) and attempted to commit suicide could be tragic at the end. Doctors treating adolescents must be conscious of the symptoms and results for sexual violence, and therefore should be concerned with the children’s normal and abnormal urogenital physiology. In India like in many other nations, child sexual exploitation is widespread so there is an increasing concern for recognizing its aspects and nuances. There is a youngster populace in India (19 percent of the total population) and a huge chunk of this populace is highly susceptible to any and all kinds of maltreatment, enslavement and abuse. Child sexual harassment, also known as sexual misconduct, is a form of sexual abuse where an adolescent or toddler is exploited by an adult or younger teenager for personal arousal.